OFDM-Based Carrier Phase Localization With Integer Ambiguity Resolution - Jai Hyung Cho; Jie Hyun Lee (IEEE Access)
This study introduces a two-stage Time Difference of Arrival (TDoA) localization method using OFDM signals with carrier-phase measurements. Unlike conventional methods, our approach uniquely resolves integer ambiguities in carrier-phase signals by combining the coarse estimates derived from multiple long-wavelength subcarrier phase differences within a single OFDM symbol. Subsequently, fine TDoA measurements from high-frequency carrier-phase signals utilize these coarse references for precise positioning. We present a maximum-likelihood estimator (MLE), analyze its performance using the Fisher information matrix and Cramér-Rao Lower bound (CRLB), and validate our method through simulations and field tests, demonstrating sub-meter accuracy and significant robustness improvements over existing techniques.